PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN METODE PEER TEACHING UNTUK MENINGKATKAN PEMAHAMAN LIMIT FUNGSI ALJABAR - Nurhayati, Aan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This study was motivated by the low understanding of students in learning mathematics on the limit material of algebraic functions. The learning process that occurs is less effective with the existence of students who have low absorption of learning materials. To overcome the low student understanding of the limit material of algebraic functions, a problem-based learning model with peer teaching was applied. The type of research used is classroom action research (PTK) using 2 cycles, each cycle consisting of 1 meeting. The research stages consist of planning (palnning), action (action), observation (observation), and reflection (reflection). The results of the research that has been done, it can be concluded that, the application of problem-based learning model with peer teaching method to improve the understanding of the limit of algebraic function in class XI MIPA 1 SMA Negeri 1 Sobang. This is evidenced by the acquisition of increased student understanding through learning outcomes in the form of written test assessment results. The acquisition of an increase from cycle 1 meeting 1 from 51.35% to 70.05% cycle 1 meeting 2. Cycle 2 meeting 1 from 70.05% to 84.65% in cycle 2 meeting 2.